Pola Komunikasi Orang Tua dengan Anak dalam Adaptasi Kelas Online di Desa Umejero Kecamatan Busungbiu pada Masa Pandemi Covid-19 - Haresvari, Made Amanda; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
During the Covid-19 pandemic, the government implemented Distance Learning or online classes from home throughout Indonesia, including in Umejero Village, Busungbiu, Singaraja. The purpose of this research is to find out how parents and children communicate in the online class adaptation that occurred during the pandemic era in Umejero. This research is descriptive qualitative research that uses theories of communication patterns between parents and children by Yusuf Syamsu, namely permissive communication patterns (liberating), authoritarian communication patterns (authoritarian), and authoritative communication patterns (democratic). Data collection techniques that are used are in-depth interviews with 6 informants consisting of 3 parents and 3 elementary school students in Umejero, documentation and observation. The results are all the theories of communication patterns by Yusuf Syamsu were used in Umejero, one family used permissive patterns, one family used authoritative patterns, and one family used combined permissive and authoritarian patterns. Keywords: Communication Pattern, Parents, Children, Distance Learning.